2011
DOI: 10.1016/s2005-2901(11)60006-x
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Blood Fluidity by Inhibition of Platelet Adhesion Using Electroacupuncture Stimulation

Abstract: Stress applied to rats is known to result in a quick decrease in blood fluidity. Although electrical acupuncture stimulation (ACU) attenuates stress responses, the influence of ACU on blood fluidity has not been well examined. In the present study, the effect of ACU on blood fluidity and platelet adhesion was examined using a Micro Channel Array Flow Analyzer and a laser scattering platelet aggregometer (PA-20), respectively. Male Wistar rats (7-8 weeks old) were used. ACU (1 Hz, 3-5 V), which causes slight mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In an experimental study in male rats, lowfrequency EA enhanced blood flow and inhibited platelet aggregation (31). The lack of an effect on coagulation/fibrinolytic markers in the physical exercise group suggests that the exercise program was not intense enough to affect these variables.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In an experimental study in male rats, lowfrequency EA enhanced blood flow and inhibited platelet aggregation (31). The lack of an effect on coagulation/fibrinolytic markers in the physical exercise group suggests that the exercise program was not intense enough to affect these variables.…”
Section: Discussionmentioning
confidence: 94%
“…In male rats, low-frequency EA increases blood flow and decreases platelet aggregation (31). Whether experimental findings can be translated into the clinical situation remains to be elucidated.…”
mentioning
confidence: 99%
“…As the effects of acupuncture vary according to the location of the stimulus (acupoint), acupuncture was applied at various locations: Zusanli (ST-36) on the outside crus superior, Sanyinjiao (SP-6) on the inside crus lower part, Hegu (LI-4) between the thumb and the forefinger of the hand, Neiguan (P-6) on the distal inside arm, and Shenshu (BL-23) on the outside dorsal spine [8]. The results showed that blood-flow time decreased significantly in the group with stimulation at the Zusanli, Hegu, and Sanyinjiao acupoints; however, no significant changes were noted in the group with stimulation at the Neiguan and Shenshu acupoints [8]. In this experiment, no differences in the numbers of leukocytes, erythrocytes, and platelets and in the percentage hematocrit value existed between the control and the experimental groups.…”
Section: Influence Of Acupuncture Stimuli On Blood Fluiditymentioning
confidence: 99%
“…Next, blood fluidity using an erythrocyte suspension was used to measure the deformability of erythrocytes [8]. The erythrocytes that were separated from the blood samples were adjusted to 30% with hematocrits, and this erythrocyte suspension's fluidity was measured using MC-FAN.…”
Section: Influence Of Acupuncture Stimuli On Blood Fluiditymentioning
confidence: 99%
See 1 more Smart Citation